Generation of femtosecond pulsed from TI:Ssapphire oscillator - Bidin, Noriah; Wan Aizuddin, Wan Razali; Saidin, Mohd. Khairi (Faculty of Science, 2009)
A Ti:Sapphire oscillator was aligned to form a Z" folded cavity. Diode pumped solid state laser with wavelength of 532 nm was employed as a pumping source. The oscillator comprised a set of mirrors including high reflectivity of 99.8% mirror and an output coupler with 5% transmission. A pair of prism was interposed into the cavity to induce mode-locked pulses. External perturbation was introduced to initiate femtopulse generation. The femtosecond pulse spectrum was found to be centered at 806.74 nm with bandwidth of 24.8 nm at full width half maximum (FWHM). The pulse duration of the signal is estimated to be as 27.56 femtosecond